2006
DOI: 10.4269/ajtmh.2006.74.69
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Land Cover and Habitat Productivity of Malaria Vectors in Western Kenyan Highlands

Abstract: We examined the effects of land cover type on survivorship and productivity of Anopheles gambiae in Kakamega in the western Kenyan highlands (elevation = 1,420-1,580 meters above sea level). Under natural conditions, An. gambiae sensu lato adults emerged only from farmland habitats, with an estimated productivity of 1.82 mosquitoes/meter(2)/week, but not from forest and swamp habitats. To determine the effects of intraspecific competition and land cover types, semi-natural larval habitats were created within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
193
1
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(216 citation statements)
references
References 26 publications
18
193
1
4
Order By: Relevance
“…The abundance of water bodies and favorable temperatures, maize plantings, extensive deforestation, or farmland have been associated with increased larval or mosquito abundance and thus increased risk for malaria transmission in human populations. [31][32][33][34] Other studies have used geographic information systems and satellite imagery to investigate environmental factors that potentially drive the dynamics of malaria vector populations [34][35][36] and other vector-borne and zoonotic diseases such as dengue fever or hantavirus. [37][38][39] It has been shown that the efficacy of control measures such as intermittent preventive treatment (IPT) can be strongly dependent on the present malaria incidence, [40][41][42] and it can be assumed that direct and contextual effects increase with malaria risk after an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of water bodies and favorable temperatures, maize plantings, extensive deforestation, or farmland have been associated with increased larval or mosquito abundance and thus increased risk for malaria transmission in human populations. [31][32][33][34] Other studies have used geographic information systems and satellite imagery to investigate environmental factors that potentially drive the dynamics of malaria vector populations [34][35][36] and other vector-borne and zoonotic diseases such as dengue fever or hantavirus. [37][38][39] It has been shown that the efficacy of control measures such as intermittent preventive treatment (IPT) can be strongly dependent on the present malaria incidence, [40][41][42] and it can be assumed that direct and contextual effects increase with malaria risk after an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] While ITNs are currently the priority strategy, there is growing interest in attacking the aquatic stages of malaria vectors with microbial larvicides, in conjunction with environmental management. 5,6,[12][13][14][15][16][17][18][19][20][21] Presently, microbial larvicides are being used in an operational context only in Dar es Salaam, in the United Republic of Tanzania. 22,23 However, in the future larvicide application will be expanded to many of the 15 countries included in the President's Malaria Initiative and this interest is likely to spread to other African countries.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The ecological features of the western highlands of Kenya support stable parasite transmission, and increasing population pressure has led to the clearance of natural swamps, massive deforestation and crop cultivation in the valley bottoms. 5,6 Because of these agricultural changes, many water bodies are now exposed to the sun and provide ideal conditions for vector proliferation and increased malaria transmission. 7 Malaria control in these highlands is based on insecticide-treated nets (ITNs), indoor-residual spraying (IRS) with insecticides and prompt and effective treatment of clinical malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in land cover and/or climate may have important effects on the distribution and intensity of mosquito-borne diseases on regional scales (e.g. Martens et ah, 1999;Lindsay & Bayoh, 2004;Zhou et al, 2004;Munga et al, 2006). Rubio-Palis and Zimmerman (1997) concluded that irrigation, clearing of tropical forest for subsistence agriculture, animal husbandry and mineral exploitation, and construction of dams complicate an ecoregional approach to classifying vector distribution in the Neotropics.…”
Section: Discussionmentioning
confidence: 99%